2019
DOI: 10.1186/s13104-019-4327-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of skin toning practices among female students in Ghana: a cross-sectional university-based survey

Abstract: Objective The use of skin toning products has a deep historical background in low and middle-income countries. Yet, there is no empirical evidence on the prevalence, and patterns of skin toning practices among university students in Ghana. This study sought to examine the prevalence, patterns and socio-demographic factors associated with skin toning practices among female university students in Ghana using a sample of 389 undergraduate female students. Results 40.9% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The study reported the prevalence of skin lightening among female undergraduate medical students of the Niger Delta University as 40.9%. This is higher than the global and African prevalence reported by Sagoe et al 7 (27.7% and 27.1%) respectively, exactly same as that reported in Ghana (40.9%) 8 but lower than the prevalence of 64.9% among Nigerian undergraduates of University of Benin 15 and the 77.3% among Nigerian traders. 10 This is also lower than the prevalence rate of 52.2% obtained in a study by Yusuf et al among health science students in Somaliland.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…The study reported the prevalence of skin lightening among female undergraduate medical students of the Niger Delta University as 40.9%. This is higher than the global and African prevalence reported by Sagoe et al 7 (27.7% and 27.1%) respectively, exactly same as that reported in Ghana (40.9%) 8 but lower than the prevalence of 64.9% among Nigerian undergraduates of University of Benin 15 and the 77.3% among Nigerian traders. 10 This is also lower than the prevalence rate of 52.2% obtained in a study by Yusuf et al among health science students in Somaliland.…”
Section: Discussionsupporting
confidence: 49%
“…7 Reported prevalence of skin toning among female university students in Ghana was 40.9%. 8 Nigeria has about the world's highest percentage of women engaged in skin lightening. According to the World Health Organization, 77% of women in Nigeria use skin lightening products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A structured questionnaire was used to gather data for this study. The questionnaire was designed by the authors after reviewing relevant literature on skin bleaching 13,15,18,21 . To ensure the reliability of the data collection tool, the questionnaire was piloted among 30 young adults in the West Gonja Municipality.…”
Section: Data Collection Tools and Proceduresmentioning
confidence: 99%
“…This growing misconception about skin bleaching has pushed most women into patronizing cosmetic agents such as kojic acid, corticosteroids, and hydroquinone-based products 15,16 . In Ghana, the prevalence of skin bleaching is reported to range 30.0-65.6% 14,17 , predominantly among females 18 . Studies on skin bleaching in Ghana are limited, especially in Northern Ghana, despite the increasing rate of skin bleaching products usage in Ghana.…”
Section: Introductionmentioning
confidence: 99%